2005
DOI: 10.1111/j.1540-6210.2005.00468.x
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Inquiry and the Search for Connectedness: Practitioners and Academics Developing Public Administration Scholarship

Abstract: Narrative Inquiry and the Search for Connectedness: Practitioners and Academics Developing Public Administration ScholarshipMaintaining a vibrant field of public administration requires ongoing efforts to link the worlds of academic researchers and practitioners. We suggest that research itself, traditionally pursued by academics, is a promising mechanism for making this connection. In particular, researchers and practitioners in public administration can do research together in a way that enhances mutual lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 48 publications
0
57
0
1
Order By: Relevance
“…For example, in an empirical project focusing on leaders of successful networks, the researchers link paradox and collaboration to better understand network management (Ospina and Saz‐Carranza ). Here, two paradoxes—unity versus diversity and confrontation versus dialogue—that emerged from narrative inquiry (Ospina and Dodge ) were used conceptually to empirically document how leaders manage paradox (Ospina and Saz‐Carranza , 431). In terms of collaborative leadership, the findings suggest that successful leaders respond in ways that honor both sides of the paradoxes.…”
Section: Investigating Collaboration Using a Paradox Lensmentioning
confidence: 99%
“…For example, in an empirical project focusing on leaders of successful networks, the researchers link paradox and collaboration to better understand network management (Ospina and Saz‐Carranza ). Here, two paradoxes—unity versus diversity and confrontation versus dialogue—that emerged from narrative inquiry (Ospina and Dodge ) were used conceptually to empirically document how leaders manage paradox (Ospina and Saz‐Carranza , 431). In terms of collaborative leadership, the findings suggest that successful leaders respond in ways that honor both sides of the paradoxes.…”
Section: Investigating Collaboration Using a Paradox Lensmentioning
confidence: 99%
“…We have tended to describe our work as involving “coproduction.” By “coproduction,” we mean, broadly, the accomplishment of research by academics and practitioners working together at each stage of the process, including conceptualization, design, fieldwork, analysis, and presentation of the work. In this journal, the term has been used by Sonia M. Ospina and Jennifer Dodge (2005b), who note that in public administration research, coproduction builds on the legacy of the early “pracademics” who sought to bring scholarship and practice closer together. A discourse of coproduction is to be found in a range of areas beyond research, including artistic, musical, and creative industries.…”
Section: Clarifying the Concept Of Coproductionmentioning
confidence: 99%
“…Ospina and Dodge (2005b) have argued in this journal that the tension between cumulative science and practice‐grounded research is a permanent threat to any aspiration to connectedness, and they frame a series of important questions about the relationships between academics and practitioners, including who produces knowledge, for whom, and for what purposes. These are questions that members of different traditions continue to struggle to come to terms with and yet influence the capacity for making connections.…”
Section: Arguments For Collaborative Researchmentioning
confidence: 99%
“…Similarly, there is a call in public sector research from the qualitative research emphasizing narrative, for example. in Ospina and Dodge (2005) to the more quantitative method-driven research on large data sets public sector leadership found, for example, in Wright et al (2012). As the Editor-in-Chief, I welcome the range of qualitative and quantitative methods that advance the understanding of public leadership in contexts throughout the world.…”
Section: Journalmentioning
confidence: 99%